Ground penetrating radar measurement of snow in Svalbard - past, present, future (SnowGPR) - Ignatiuk, Dariusz; Dunse, Thorben; Gallet, Jean-Charles; Girod, Luc; Grabiec, Mariusz; Kepski, Daniel; Kohler, Jack; Laska, Michal; Luks, Bartlomiej; van Pelt, Ward; Petterson, Rickard; Pohjola, Veijo; et al. (Svalbard Integrated Arctic Earth Observing System, 2023)
This is chapter 5 of the State of Environmental Science in Svalbard (SESS) report 2022. Snowpack covers 60-100% of all land in Svalbard, depending on the season, and it is very sensitive to changes in climate. Knowledge about the snowpack is important not just in itself, but also to understand how snow cover affects other components of Svalbard’s natural environment – land, sea, permafrost, glaciers, and the ecosystems that they support. Monitoring the evolution of Svalbard’s snow cover will be crucial as the world’s climate continues to warm. Ground-penetrating radars (GPRs) towed by snowmobile across glaciers and snowfields provide vital information about snowpack thickness and structure. Ideally, such surveys should be repeated annually for continuous monitoring of climate-induced change. Three decades ago, a GPR programme catalogued regional variations in snow accumulation. This should be repeated and expanded to cover all of Svalbard. The GPR method should also be further developed e.g. by mounting GPRs on drones, giving access to parts of glaciers that are too dangerous for researchers to visit. Lastly, women are encouraged to join the field of GPR-based research on snow. Most of the GPR data collected so far are not currently available in any data repository. The comprehensive compilation of available studies presented in this report, and the recommendations for metadata and data quality, are important first steps to making GPR data more accessible.